Defining the Jacobean Church : the politics of religious controversy, 1603-1625 - Prior, Charles W. A. (Cambridge studies in early modern British history., 2005)
This book proposes a new model for understanding religious debates in the churches of England and Scotland between 1603 and 1625. It argues that rival interpretations of scripture, pagan, and civil history and the sources central to the Christian tradition lay at the heart of disputes between contrasting ecclesiological visions.